Investigation of tool wear in the turning of Inconel 718 superalloy in terms of process performance and productivity enhancement. (February 2018) - Grzesik, W.; Niesłony, P.; Habrat, W.; Sieniawski, J.; Laskowski, P.
Abstract: This paper contributes to broadening the knowledge regarding cutting tool wear in the finish turning operations of nickel-chromium-based superalloy Inconel 718. Three cutting tools coated with heat isolating TiAlN/AlTiN layers with different stoichiometry ratios recommended as specially designed cutting tools for aerospace industry applications are tested. The primary comparison of tool wear resistance was based on the wear curves related to the cutting time and the removed material volume. The basic study include the modeling of wear progress and examining tool wear scars based on SME images and EDX analysis. In addition, tool wear progress was recorded along with continuous measurements of cutting forces and determination of relevant amount of the specific cutting energy and the friction coefficient. Highlights: Tool wear of AlTiN and TIAlN coated cutting tool inserts when turning Inconel 718 superalloy was investigated. Tool wear curves as functions of the cutting time and removed material volume are presented. Modelling of tool wear in terms of the cutting time and removed material volume is proposed. Tool wear mechanisms concentrated on the tool corner related to finish turning operations are explored and discussed. The relationships between tool wear and cutting force components and specific cutting energy are determined.